1983
DOI: 10.1161/01.hyp.5.4.545
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma catecholamines in hypertensives with primary glomerular diseases.

Abstract: SUMMARY Supine plasma concentration of norepinephrine (PNE), epinephrine (PE), and aldosterone (PA), plasma renin activity (PRA), and blood volume (BV) were measured in 25 normotensive and 11 hypertensive patients with biopsy-proven glomerulonephritis who had serum creatinine concentrations of less than 1.6 mg/dl, and in 20 normotensive control subjects. PNE and PE were measured according to the trihydroxyindol method using high pressure liquid chromatography. Renal clearances of p-aminohippurate (C PAH ) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 34 publications
2
39
1
1
Order By: Relevance
“…15,16 These early observations were substantiated by a pronounced hypotensive effect in response to adrenergic inhibition with clonidine 17 or debrisoquine. 18 In 1992, Converse et al 19 first reported that muscle sympathetic nerve activity, as assessed by clinical microneurography, is increased in patients who have ESRD and undergo hemodialysis.…”
Section: Sympathetic Activity In Patients With Crfmentioning
confidence: 92%
“…15,16 These early observations were substantiated by a pronounced hypotensive effect in response to adrenergic inhibition with clonidine 17 or debrisoquine. 18 In 1992, Converse et al 19 first reported that muscle sympathetic nerve activity, as assessed by clinical microneurography, is increased in patients who have ESRD and undergo hemodialysis.…”
Section: Sympathetic Activity In Patients With Crfmentioning
confidence: 92%
“…Key Words: chronic renal failure Ⅲ microneurography Ⅲ sympathetic nervous system A dvanced renal failure is accompanied by a marked activation of sympathetic cardiovascular influences, as documented by the increase in the circulating plasma levels of norepinephrine, the elevated number of sympathetic neural bursts recorded in the peroneal nerve via the microneurographic technique, and the augmented oscillations in the high-frequency band of the heart rate power spectra. [1][2][3][4][5][6][7][8][9][10][11][12][13] Whether the sympathetic activation also characterizes the earlier clinical phases of the renal failure state is not clear, however. This is because in the few studies performed so far in patients with mild renal disease, the population sample was small, and the plasma levels of norepinephrine showed inconsistent changes.…”
mentioning
confidence: 99%
“…Sympathetic activation has been demonstrated to play an important role in the pathogenesis of hypertension associated with CKD. 1,2 Clinical studies have demonstrated that plasma catecholamines were elevated 3 and muscle sympathetic nerve activity was enhanced 4,5 in CKD patients, whose blood pressure decreased pronouncedly with adrenergic inhibition by clonidine. 6 Furthermore, moxonidine, a central sympatholytic agent, was shown to reduce urinary albumin excretion associated with huge depressor effects in patients with essential hypertension with microalbuminuria.…”
mentioning
confidence: 99%